Adaptive silviculture for climate change in the Great Lakes- St. Lawrence Forest Region of Canada: Background and design of a long-term experiment - Nelson Thiffault; Jeff Fera; Michael K. Hoepting; Trevor Jones; Amy Wotherspoon (The Forestry Chronicle)
We present the implementation of the Adaptive Silviculture for Climate Change (ASCC) initiative at the Petawawa Research Forest (PRF) in Ontario, Canada. The study addresses the urgent need for adaptive forest management strategies in response to climate change by examining silvicultural treatments aimed at mitigating its impacts on forest ecosystems. It addresses the complex interplay between climate change projections, regional climate characteristics, and forest management practices for pine dominated forests in the Great Lakes-St. Lawrence Forest region of Canada, underscoring the importance of adaptive approaches in sustaining forest ecosystems. We outline the design and objectives of five distinct treatments—control, business-as-usual, resistance, resilience, and transition—implemented over 4 replicate blocks on a 212-ha area at the PRF. We provide detailed descriptions of each treatment’s management objectives, desired future conditions, and silvicultural strategies. We conclude by summarizing planned research efforts, including seedling survival assessments, phenological monitoring, and measuring treatment impact on fuel loads. By addressing the challenges and opportunities of climate change as part of an international research network, this research will contribute to a deeper understanding of forest ecosystem responses to climate change and inform adaptive management strategies for sustainable forest management.